Identification of the Six-RNA-Binding Protein Signature for Prognosis Prediction in Bladder Cancer - Wu, Yucai; Liu, Yi; He, Anbang; Guan, Bao; He, Shiming; Zhang, Cuijian; Kang, Zhengjun; Gong, Yanqing; Li, Xuesong; Zhou, Liqun (Frontiers in Genetics, 2020)
RNA-binding proteins (RBPs) are kind of gene regulatory factors that presented significant biology effect in the initiation and development of various tumors, including bladder cancer (BLCA). However, RBPs-based prognosis signature for BLCA has not been investigated. In this study we attempted to develop a RBPs-based classifier to predict over survival (OS) for BLCA based on transcriptome analysis. We extracted data of BLCA patients from The Cancer Genome Atlas database (TCGA) and UCSC xena. Finally, a total of 398 cases without missing clinical data were enrolled and 6 RBPs (FLNA, HSPG2, AHNAK, FASTKD3, POU5F1, and PCSK9) associated with OS of BLCA were identified through univariate and multivariate Cox regression analysis. Online analyses and immunohistochemistry validated the prognostic value and expression of 6 RBPs. Risk scores were calculated to divide patients into high-risk and low-risk level and patients in the high-risk group tended to have a poor prognosis. In addition, the receiver operating character (ROC) curve analysis was performed to assess the prognostic value of RBPs and the area under curves (AUCs) values were 0.711 and 0.706 respectively in the training set and validating set. The findings were further validated in an external validation set. Subsequently, the 6-RBPs-based signature and pathological stage were used to construct the nomogram to predict the 3- and 5-year OS of BLCA patients. Also, this six-RBPs-based signature was highly related to recurrence free survival of BLCA. Weighted correlation network analysis (WGCNA) combined with functional enrichment analysis contributed to study the potential pathways of six RBPs, including keratinocyte differentiation, RHO GTPases activate PNKs, epithelial tube morphogenesis, establishment or maintenance of cell polarity and so on. In summary, the 6-RBPs-based signature holds the potentiality to serve as a novel prognostic predictor of OS for BLCA.